The Impact of Huyula Social Capital In Sustainable Agricultural Land Management In Lamahu Village Bilato District Gorontalo Regency - Nanda Melan Adam; Wawan K Tolinggi; Echan Adam (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2025)
Purpose : This study aims to examine in depth the impact of Huyula social capital in sustainable agricultural land management in Lamahu Village, Bilato District, Gorontalo Regency. Methodology : This study uses a qualitative approach with ethnographic methods. Results : The results of the study indicate that Huyula practices are able to increase agricultural productivity through collective work, reduce operational costs, and strengthen social relations between farmers. Huyula has also been proven to be a social mechanism that supports the sustainability of efficient and sustainable land management. Findings : The key finding of this study is that Huyula functions not only as a mutual cooperation system, but also as social capital that directly impacts agricultural efficiency, social resilience, and sustainable land management. Novelty : The novelty of this study lies in the disclosure of the specific role of Huyula as social capital that is able to integrate socio-cultural aspects with sustainable agricultural practices. This study offers a new perspective on how local traditions can become strategic instruments in contemporary agricultural development. Originality : The originality of the study is reflected in the focus of the study which places Huyula as a main pillar in the sustainable agricultural system in Lamahu Village. This study contributes new knowledge regarding the relationship between local wisdom, social capital, and agricultural sustainability, which has not previously been studied in depth in the context of the Gorontalo region. Conclusion : The study concludes that Huyula social capital has a significant impact in supporting a sustainable agricultural system. Huyula is able to increase work efficiency, strengthen social solidarity, and maintain the sustainability of land management. This practice not only functions as an agricultural strategy, but also as a means of preserving local culture that remains relevant amidst modernization. Type of Paper : Research article.